Diabetes mellitus and the risk of cholangiocarcinoma: an updated meta-analysis - Li, Junshan; Han, Tianjie; Xu, Linlin; Luan, Xiaotian (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Introduction : A number of studies have shown that diabetes mellitus is implicated in susceptibility to several cancers. However, the relationship between diabetes and cholangiocarcinoma remain unclear. Aim: To quantitatively assess the relationship between diabetes and incidence of cholangiocarcinoma in cohort and case-control studies. Material and methods : A literature search was performed for entries from 1996 to 2014 using the PubMed and EMBASE databases. Studies were included if they reported odds ratios (OR) and corresponding 95% CI of cholangiocarcinoma with respect to diabetes mellitus. Results: Twenty studies met the inclusion criteria, which included fifteen case-control studies and five cohort studies from Asia (n = 11), the United States (n = 5), and Europe (n = 4). Compared with individuals without diabetes, the pooled OR of cholangiocarcinoma was 1.74 (95% CI: 1.62–1.87, p = 0.568 for heterogeneity) for patients with diabetes, ICC (summary RR, 1.93; 95% CI: 1.65–2.25; p = 0.037 for heterogeneity), and ECC (summary RR, 1.66; 95% CI: 1.39–1.98; p = 0.001 for heterogeneity). The funnel plot revealed no evidence for publication bias concerning diabetes and the risk of CC (including ICC and ECC). Conclusions : The findings from this meta-analysis suggest that diabetes may increase the risk of cholangiocarcinoma. This relationship needs to be confirmed by further follow-up studies.